Scanning probe microscopy based characterization of battery materials, interfaces, and processes. (November 2019) - Kempaiah, Ravindra; Vasudevamurthy, Gokul; Subramanian, Arunkumar
Abstract: Increasing demand for sustainable battery technologies has necessitated substantive global research efforts towards delivering improvements in terms of both, the underlying battery materials and processes. Due to favorable attributes such as high gravimetric energy density, batteries based broadly on inorganic-ion, and more specifically on Lithium-ion (Li-ion), electrochemistry have emerged as the technologies of choice for current and next-generation consumer electronic devices and electric automobiles. Improvements in critical system metrics such as energy/power density, cycle-life, cost, safety, and technological sustainability rely heavily on multi-parameter, multi-scale, and multi-physics optimization of the materials, interfaces, and processes that constitute a battery system. Over the past decade, Scanning Probe Microscopy (SPM) techniques have delivered important solutions for addressing these technological challenges through new characterization tools at the atomic-to-nanoscale. This article presents a comprehensive review of these SPM techniques of relevance for the battery systems. Specifically, each SPM operation mode of relevance, which include atomic force microscopy, electrochemical atomic force microscopy, Kelvin probe force microscopy, electrochemical strain microscopy, scanning ion conductance microscopy, and scanning electrochemical microscopy, have been discussed in terms of their state-of-the-art, applications, advantages, limitations, and future directions. Furthermore, a detailed analysis of the following information and insights revealed by these methodologies has been provided: ionic transport and diffusion dynamics, electrochemical activity, surface and interfacial studies, morphological and dimensional changes, and evolution of mechanical properties/their degradation. Graphical abstract: Image 1 Highlights: SPM based characterization of battery materials, interfaces, and processes is reviewed. Applications discussed include ionic transport mechanisms and electrochemical activity. Reports on electrode mechanics and its surface/SEI evolution are reviewed. Battery relevant SPM modes highlighted include AFM, EC-AFM, KPFM, ESM, SICM, & SECM.